A case report on large retroperitoneal liposarcoma - Chaudhari, Sandipkumar; Patel, Brijesh; Patel, Jimitkumar; Chaudhary, Sonalben (International Surgery Journal, 2022)
Even though rare, retroperitoneal masses evoke interest for so many reasons. They involve a wide variety of tumor types, both malignant and benign, making the diagnosis a challenge. Many tumor types have different clinical behaviors and treatments. Surgical resection is always challenging technically with no fixed steps of resection. The <1% of neoplasms are soft tissue sarcomas in humans. Liposarcoma is the most common retroperitoneal sarcoma among the retroperitoneal malignant tumors. More often than not, patients report late to the hospital due to the very slow growth and the onset of a few late symptoms, patients usually present at a late stage to the health care. Therefore, in most cases, the tumor is known to have reached enormous sizes and might have infiltrated vital structures. Here, we reported a case of large retroperitoneal liposarcoma weighing more than 8 kgs.